2017
DOI: 10.1080/1828051x.2017.1350121
|View full text |Cite
|
Sign up to set email alerts
|

Variability of fibre quality on Chinese Alashan Left Banner White Cashmere goat

Abstract: The heritability and the phenotypic and genetic correlations of down weight (DW), down fibre diameter (DFD), and coefficient of variation of the down fibre diameter (CVDFD) of Chinese Alashan Left Banner White Cashmere goat were estimated on 1375 one-year-old animals, born in 2009, 2011 and 2013 and bred at the Station for Livestock Improvement of Alashan (Left Banner, Inner Mongolia, P.R. China). For all traits, significant effects were for sex, cohort and sex-cohort interaction (p < .001). The heritability f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
2
5
0
1
Order By: Relevance
“…Similarly, McGregor and Butler observed an increasing trend of CP with age in Australian goats, though the maximum value appeared at six years old (McGregor and Butler 2008a). The CP of males in this study was much higher than that of females, echoing the results of previous studies (Rischkowsky and Momen 2012;Bai et al 2015;Pallotti et al 2018;Wani et al 2018). However, Newman and Paterson (1996) explained that the cashmere production of males was lower than that of females for New Zealand cashmere goats.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similarly, McGregor and Butler observed an increasing trend of CP with age in Australian goats, though the maximum value appeared at six years old (McGregor and Butler 2008a). The CP of males in this study was much higher than that of females, echoing the results of previous studies (Rischkowsky and Momen 2012;Bai et al 2015;Pallotti et al 2018;Wani et al 2018). However, Newman and Paterson (1996) explained that the cashmere production of males was lower than that of females for New Zealand cashmere goats.…”
Section: Discussionsupporting
confidence: 86%
“…Most studies (Ferreira et al 2014;Visser and Marle-K€ oster 2014) have demonstrated positive genetic and phenotypic correlations between CP and MFD, which is consistent with the results of this study, in which cashmere production increased 31.67 g per 1 mm increase in mean fibre diameter. Nevertheless, a study performed by Stefano Pallotti showed that CP had a negative genetic correlation and positive phenotypic correlation in Chinese Alashan Left Banner White Cashmere goats, which may be explained by the diverse breeds and data structures (Pallotti et al 2018). The regression coefficient of FL in IMCGs was 26.50 g/ cm, which confirms the positive genetic correlation between CP and FL found in previous studies (Zhou et al 2003;Bai et al 2006).…”
Section: Discussionsupporting
confidence: 78%
“…An example of breed development through divergence from a common genetic pool is the Small Spitz breeds. Phylogenetically, the Small Spitz clade (Figure 2) includes the Pomeranian, American Eskimo, and Volpino Italiano (Figure 1p An additional example of genetic data superseding historical lore is that of the Segugio Italiano breed which, since 1989, has been classified as two separate breeds, the Pelo Raso (smooth haired) ( Figure 1j) and Pelo Forte (rough haired) ( Figure 1k) (Pallotti et al, 2017). Early writings by the Greek historian Arrian (c. 92-175 AD) describe "Segusian hounds" as "shaggy" (Arrian, 1831), suggesting that the original breed may have more closely resembled the Pelo Forte of today.…”
Section: Italian Dog Breedsmentioning
confidence: 99%
“…Cashmere fibre is generally non-medullated and has a mean maximum diameter of 19 µm and the coefficient of variation around the mean should not exceed 24% [5]. The average CVFD values for Mongolian breeds of cashmere goats was 22.5 ± 0.04% with an individual range of 17.0-26.9 %, showing less variation compared to Alashan white cashmere goats of Inner Mongolia, China, where CVFD ranged from 27.09% to 41.39% [10]. Cashmere samples with a coefficient of variability up to ≤24% of the diameter of cashmere fibres accounted for 80.0-88.9% of all samples.…”
Section: Discussionmentioning
confidence: 99%